Biotransformation studies of cresol red by Absidia spinosa M15. (1st May 2016) - Kristanti, Risky Ayu; Fikri Ahmad Zubir, Meor Mohd; Hadibarata, Tony
Abstract: Cresol Red, a commercial dye that used widely to color nylon, wool, cotton, and polyacrylonitrile-modified nylon in the massive textile manufacture is toxic recalcitrant. Absidia spinosa M15, a novel fungal strain isolated from a tropical rain forest, was found to decolorize Cresol Red 65% within 30 d under agitation condition. UV–Vis spectroscopy, TLC analysis and mass spectra of samples after decolorization process in culture medium confirmed final decolorization of Cresol Red. Two metabolites were identified in the treated medium: benzeneacetic acid (tR 9.6 min and m/z 136) and benzoic acid (tR 5.7 min and m/z 122). Laccase showed the significant activity (133.8 U/L) in biomass obtained at the end of experiment demonstrates role of the enzyme in the decolorization process. Graphical abstract: A degradation pathway of Cresol Red dye by Absidia spinosa M15. Highlights: Cresol Red was degraded by Absidia spinosa M15 in aqueous solution. Two routes degradation of Cresol Red were elucidated. Laccase is an enzyme that plays an important role in the transformation of Cresol Red.